2021
DOI: 10.2147/cmar.s313517
|View full text |Cite
|
Sign up to set email alerts
|

CA19-9 Level to Serum γ-Glutamyltransferase as a Potential Prognostic Biomarker in Patients with Pancreatic Head Carcinoma

Abstract: Background The aim of this study was to reduce the influence of biliary obstruction on carbohydrate antigen 19-9 level (CA19-9) by introducing the CA19-9 level to serum γ-glutamyltransferase (GGT) ratio as an indicator, and ultimately to reveal the correlation between CA19-9/GGT and the prognosis of patients with pancreatic head carcinoma (PHC). Methods A total of 339 enrolled patients who underwent pancreatoduodenectomy for PHC in Beijing ChaoYang Hospital from January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Recent studies have found a correlation between elevated serum levels of GGT and various digestive tumors, including pancreatic head carcinoma (Lyu et al, 2021), colorectal carcinoma (Gong et al, 2021), and gallbladder carcinoma (Su et al, 2021). A linear association was also detected between increased levels of GGT and cancer-related deaths (Albhaisi and Qayyum, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have found a correlation between elevated serum levels of GGT and various digestive tumors, including pancreatic head carcinoma (Lyu et al, 2021), colorectal carcinoma (Gong et al, 2021), and gallbladder carcinoma (Su et al, 2021). A linear association was also detected between increased levels of GGT and cancer-related deaths (Albhaisi and Qayyum, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…It is suggested that this may play a functional modulatory role, in terms of inhibiting or enhancing the activity of associated enzymes 45 . So far, in an unrelated examination, possible use of the ratio of CA19-9 to total serum GGT is suggested for the prediction of recurrence and long-term prognosis in patients with pancreatic head carcinoma and cholangiocarcinoma 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…And the high levels of Ca19.9 is a marker not only for determining the incidence of pancreatic tumors, but perhaps there are neighboring organs that have been invaded by these tumors, such as the liver, so this indicator is of great importance in determining these cancers [30]. Lyu et al, (2021) has been proven a high percentage in levels of CA19.9 for patients with pancreatic tumors and that this indicator is of great importance in determining glandular tumors, especially pancreatic tumors. While in the benign tumors of the pancreas, there were average levels in the proportions of measurements of CA19.9 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Lyu et al, (2021) has been proven a high percentage in levels of CA19.9 for patients with pancreatic tumors and that this indicator is of great importance in determining glandular tumors, especially pancreatic tumors. While in the benign tumors of the pancreas, there were average levels in the proportions of measurements of CA19.9 [31]. Poruk et al, (2013) explained there is a high accuracy and sensitivity in using the CI 19.9 marker in determining the incidence of pancreatic cancer compared to benign tumors [32].…”
Section: Discussionmentioning
confidence: 99%